Topology Optimization Design of Transmission Case Housing Used in Electric Vehicle - Zhang Qing; Li Hongbiao; Zhou Qia; Yan Huidong; Guo Wentian; Yang Xianxue (Jixie chuandong, 2017)
Aiming at the structure of transmission case housing used in electric vehicle,the topology optimization analysis of transmission case housing used in electric vehicle,including the external and internal reinforcing plates and outside profile is conducted by using the method of topology optimization analysis from the forward design. In the optimization,the minimum weighted compliance is set as the optimization objective and volume fraction,displacement,stress,modal frequency and machining technology as constrains. Based on the topology optimization result,the optimization design of transmission case housing is carried out with considering the requirements of assembly,lubrication and cooling. Furthermore,the stresses state and modal frequency of the transmission case housing is also calculated in order to verify its structural strength and vibration performance. The analysis results show that the structural strength and modal frequency of the optimized transmission are higher than the design index,the optimization design of the complicated transmission case housing structure is realized.